THE URGENCY OF PRAYER IN LIFE BASED ON THE AL-QUR'AN PERSPECTIVE - Abid Nurhuda; Inamul Hasan Ansori; Ts. Engku Shahrulerizal Bin Engku Ab Rahman (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Prayer is one of the pillars, supports, and foundations of a building called the religion of Islam. The conditions, obligations, and pillars must be fulfilled for the perfect reward. Movements become a system in life which is heart, mind, and body as a manifestation of one's faith, but nowadays, many Muslims leave Prayer due to many factors, one of which is not knowing the virtue of Prayer. Therefore, the purpose of this study is to describe the urgency of Prayer in life according to the Qur'an perspective. The method used is literature study from books, journals, and the internet by collecting data using careful observation techniques. Then document and analyze the contents, and the last is concluding. The results of the study show that the Urgency of Prayer in Life based on the Qur'an perspective Prevents heinous and evil deeds, Shows brotherhood and equality between human beings, Trains Discipline, Builds physical and spiritual health, and Accustoms to patience and trust.